The Effect of Social Media Engagement on Brand Loyalty in the Digital Economy - Antonius Ary Setyawan; Wahyudin Rahman; Eko Wahyu Widayat; Imam Jayanto; Dian Parwati (Jurnal Manajemen dan Pemasaran Digital, 2026)
This study aims to analyze the effect of social media engagement on brand loyalty in the digital economy through a literature review approach. The rapid development of digital technology and social media platforms has significantly transformed consumer behavior and business communication patterns. Social media has become an essential strategic tool for organizations to establish relationships with customers and strengthen their market position. Therefore, understanding the relationship between social media engagement and brand loyalty has become increasingly important in the current digital environment. This study employed a literature review method by collecting and analyzing relevant studies published between 2015 and 2025 from academic databases and reputable journals. The analysis process involved identifying, evaluating, and synthesizing previous research findings related to social media engagement and brand loyalty. The findings indicate that social media engagement positively influences brand loyalty through emotional attachment, customer participation, and interactive communication processes. In addition, variables such as brand trust, customer experience, content quality, and online community participation strengthen the relationship between social media engagement and loyalty. The study concludes that effective social media engagement strategies contribute significantly to maintaining long-term customer relationships and enhancing sustainable competitive advantages in the digital economy.